2021
DOI: 10.3390/antiox10030483
|View full text |Cite
|
Sign up to set email alerts
|

CFTR Modulator Therapy with Lumacaftor/Ivacaftor Alters Plasma Concentrations of Lipid-Soluble Vitamins A and E in Patients with Cystic Fibrosis

Abstract: Rationale: Cystic fibrosis (CF), caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, leads to impaired pancreatic function and therefore reduced intestinal absorption of lipids and fat-soluble vitamins especially in patients with CF developing pancreatic insufficiency (PI). Previous studies showed that CFTR modulator therapy with lumacaftor-ivacaftor (LUM/IVA) in Phe508del-homozygous patients with CF results in improvement of pulmonary disease and thriving. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 67 publications
1
38
0
Order By: Relevance
“…Although such work has not been done on elexacaftor/tezacaftor/ivacaftor, evidence indicates that monotherapy with ivacaftor substantially improves intestinal absorption in CF patients through a variety of means, including reversal of pancreatic insufficiency, 2 increased intestinal pH, 5 and decreased inflammation. 6 Recently, Sommerburg et al 7 found that therapy with lumacaftor/ivacaftor significantly increased patients' serum vitamin A levels, indicating that improved intestinal function includes increased absorption of vitamin A.…”
mentioning
confidence: 99%
“…Although such work has not been done on elexacaftor/tezacaftor/ivacaftor, evidence indicates that monotherapy with ivacaftor substantially improves intestinal absorption in CF patients through a variety of means, including reversal of pancreatic insufficiency, 2 increased intestinal pH, 5 and decreased inflammation. 6 Recently, Sommerburg et al 7 found that therapy with lumacaftor/ivacaftor significantly increased patients' serum vitamin A levels, indicating that improved intestinal function includes increased absorption of vitamin A.…”
mentioning
confidence: 99%
“…In the current era, frank micronutrient deficiencies of vitamin A and vitamin E are rarely encountered in patients with CF, presumably owing to early diagnosis and initiation of pancreatic enzymes, CF‐specific vitamin supplementation, and possibly improved absorption with HEMs. On the contrary, instances of elevated vitamin levels are now seen 12–17 . Also, once solely considered as micronutrients, our latest understanding of the role of fat‐soluble vitamins and trace minerals has evolved.…”
Section: Introductionmentioning
confidence: 99%
“…For example, changes in fat soluble vitamins. In 45 patients, over age 2 years who had treatment with LUM/IVA for one year, the following was seen, no changes in Vitamin D levels or Retinol, an increase in international normalized ratio (INR), and a decrease in Vitamin E 16 . By two years of treatment, there were no additional changes in Vitamin D or INR, yet retinol increased, and Vitamin E decreased 16 .…”
Section: Lumacaftor/ivacaftormentioning
confidence: 99%